Characteristics and Clinical Outcomes of Patients With Spontaneous Coronary Artery Dissection. Issue 10 (21st May 2019) - Clare, Ryan; Duan, Lewei; Phan, Derek; Moore, Naing; Jorgensen, Michael; Ichiuji, Anne; Shen, Albert Y.; Lee, Ming‐Sum
Abstract : Background: The goal of this study is to report the characteristics and long‐term clinical outcomes of patients with spontaneous coronary artery dissection (SCAD) and to identify factors associated with recurrent SCAD. Methods and Results: This is a retrospective cohort study that included patients who underwent coronary angiography for evaluation of acute myocardial infarction between 2006 and 2016. Among 26 598 patients hospitalized with a principal diagnosis of acute myocardial infarction, 208 (0.78%) were diagnosed with SCAD. Patients with SCAD were younger (49.0±11.6 versus 65.6±12.2 years) and more likely to be women (88.9% versus 31.6%). Atherosclerotic risk factors, such as hypertension, hyperlipidemia, obesity, and diabetes mellitus, were less prevalent. Median follow‐up was 4.7 years. Mortality was lower in patients with SCAD (1‐year mortality: 2.4% versus 8.8%; P <0.001). After using propensity score matching to control for differences in age, sex, and comorbidities, the difference in mortality was no longer present, suggesting that lower mortality in patients with SCAD is attributed primarily to their baseline characteristics. Recurrent SCAD occurred in 22 patients (10.6%). Multivariate Cox regression modeling showed concomitant fibromuscular dysplasia (hazard ratio, 5.1; 95% CI, 1.6–15.8; P =0.005) and migraine headaches (hazard ratio, 3.4; 95% CI, 1.4–8.4; P =0.008) to be associated with increased risk of recurrent SCAD. Conclusions: Among patients with acute myocardial infarction, patients with SCAD have a lower risk of mortality, which is attributed primarily to their younger age, female sex, and low prevalence of atherosclerotic risk factors. Risk of recurrent SCAD persists years after the initial presentation. Patients with fibromuscular dysplasia and migraine are at higher risk for recurrent SCAD.